Authority of the Financial Transaction Analysis Reporting Center in Tracing Hidden Trading Crimes - A.A. Ngurah Oka Yudistira Darmadi; Nyoman Satyayudha Dananjaya (Fakultas Hukum, Universitas Warmadewa, 2024)
The search for money resulting from money laundering crimes carried out by the Financial Transaction Analysis Reporting Center regarding cases of illegal trading in Indonesia is very difficult to find or trace, in this case the stock game only involves guessing the rising or falling graph and in guessing the name of the stock is not given. up and down. From this game, the trading dealer makes a profit of 80% of the victim's losses and the remaining 20% ​​goes to the illegal trading application. Let's take a look back at this trading, everyone wants instant wealth in a short period of time and is sure to get it quickly just by guessing the rising or falling graph in this stock game, who would have thought that this stock game has been regulated by the trading bookie of the stock game and The trading bookie also determines whether we win or lose. The trading dealer deliberately gives us the first win in this stock trading game so that we continue playing and even sell our assets such as houses, cars and others so that we can multiply them. When placing a large deposit, that is where the trading dealer makes the player lose and this is regulated by the dealer. In this case, the Financial Transaction Analysis Reporting Center investigated the confiscation and impoverishment of movable and immovable, tangible or intangible assets obtained directly or indirectly carried out by affiliates in connection with criminal cases of money laundering which are regulated in Law 8 of 2010 concerning prevention. and eradicating money laundering crimes. However, the financial transaction analysis reporting center is not given more authority in investigations or investigations but is only given the authority to provide reports on analysis results and audit analysis results only.